APLIKASI MODEL PEMBELAJARAN OME-AKE DALAM PENINGKATAN KEAKTIFAN BELAJAR PESERTA DIDIK DI MTS. AL-ARIEF JATE GILI GENTING SUMENEP - Achmad Abdul Munif; Mokh. Fakhruddin S; Tatak Winata (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2020)
This study began with the OME AKE learning model applied at MTs Al-Arief Jati Gili Genting Sumenep Madura, students were active in learning, even academic and non-academic achievements of students were very good. The study of this research is the application of the OME AKE learning model in MTs. Al-Arief Jate Gili Genteng Sumenep. This study uses a qualitative approach to the type of field research (field research). Steps The application of the OME AKE learning model in increasing the learning activeness of students at MTs Al-Arief Jate-Gili Genting-Sumenep runs according to the educational process standards. In learning, it refers to the syntax that is determined, with the first steps being learning orientation, modeling, topic exploration, analysis and problem solving, communicating the results and evaluation. The implementation of the OME AKE learning model in increasing student learning activeness is in children's learning being invited to do orientation or introduction to learning material, especially from the aspect of knowledge, after that children play a role according to their respective tasks, the children then analyze the material in detail, after the analysis is done then the results are conveyed to his friends in the form of presentations in groups and in class, the teacher then gives an evaluation of the process and results of the students. Students actively learn: such as paying attention (visual activities), listening, discussing, students 'readiness to ask questions, students' courage, listening and solving problems (mental activities).